Лучшие помощники
- Megamozg 2205 б
- Matalya1 1800 б
- DevAdmin 1720 б
- arkasha_bortnikov 895 б
- Dwayne_Johnson 860 б
Let's simplify the equation step by step:
First, we can combine the first two terms using the quotient rule of logarithms:
log²2x - 4log2x + 3 = log₂((2x)² / 2⁴) + 3 = log₂(x² / 16) + 3
Now we can use the fact that log₂(a) + log₂(b) = log₂(ab) to combine the terms inside the logarithm:
log₂(x² / 16) + 3 = log₂(x²) - log₂(16) + 3 = 2log₂(x) - 4 + 3 = 2log₂(x) - 1
So our equation becomes:
2log₂(x) - 1 = 0
We can solve for log₂(x) by adding 1 to both sides:
2log₂(x) = 1
log₂(x) = 1/2
Finally, we can solve for x by taking the inverse logarithm of both sides:
x = 2^(log₂(x)) = 2^(1/2) = √2
Therefore, the solution to the equation is x = √2.
First, we can combine the first two terms using the quotient rule of logarithms:
log²2x - 4log2x + 3 = log₂((2x)² / 2⁴) + 3 = log₂(x² / 16) + 3
Now we can use the fact that log₂(a) + log₂(b) = log₂(ab) to combine the terms inside the logarithm:
log₂(x² / 16) + 3 = log₂(x²) - log₂(16) + 3 = 2log₂(x) - 4 + 3 = 2log₂(x) - 1
So our equation becomes:
2log₂(x) - 1 = 0
We can solve for log₂(x) by adding 1 to both sides:
2log₂(x) = 1
log₂(x) = 1/2
Finally, we can solve for x by taking the inverse logarithm of both sides:
x = 2^(log₂(x)) = 2^(1/2) = √2
Therefore, the solution to the equation is x = √2.
0
·
Хороший ответ
23 июня 2023 18:51
Остались вопросы?